Assisted reproductive technology treatment and risk of breast cancer: a population-based cohort study. Issue 12 (28th September 2021) - Vassard, D; Pinborg, A; Kamper-Jørgensen, M; Lyng Forman, J; Glazer, C H; Kroman, N; Schmidt, L
Abstract: STUDY QUESTION: Is there an increased risk of breast cancer among women after ART treatment including ovarian hormone stimulation? SUMMARY ANSWER: The risk of breast cancer was slightly increased among women after ART treatment compared to age-matched, untreated women in the background population, and the risk was further increased among women initiating ART treatment when aged 40+ years. WHAT IS KNOWN ALREADY: The majority of breast cancer cases are sensitive to oestrogen, and ovarian hormone stimulation has been suggested to increase the risk of breast cancer by influencing endogenous oestrogen levels. Previous studies on ART treatment and breast cancer have varied in their findings, but several studies have small sample sizes or lack follow-up time and/or confounder adjustment. Recent childbirth, nulliparity and higher socio-economic status are breast cancer risk factors and the latter two are also associated with initiating ART treatment. STUDY DESIGN, SIZE, DURATION: The Danish National ART-Couple II (DANAC II) cohort includes women treated with ART at public and private fertility clinics in 1994–2016. PARTICIPANTS/MATERIALS, SETTING, METHODS: Women with no cancer prior to ART treatment were included (n = 61 579). Women from the background population with similar age and no prior history of ART treatment were randomly selected as comparisons (n = 579 760). The baseline mean age was 33.1 years (range 18–46 years). Results are presented as hazard ratios (HRs) with corresponding CIs. MAIN RESULTS AND THE ROLE OF CHANCE: During follow-up (median 9.69 years among ART-treated and 9.28 years among untreated), 5861 women were diagnosed with breast cancer, 695 among ART-treated and 5166 among untreated women (1.1% versus 0.9%, P < 0.0001). Using Cox regression analyses adjusted for nulliparity, educational level, partnership status, year, maternal breast cancer and age, the risk of breast cancer was slightly increased among women treated with ART (HR 1.14, 95% CI 1.12–1.16). All causes of infertility were slightly associated with breast cancer risk after ART treatment. The risk of breast cancer increased with higher age at ART treatment initiation and was highest among women initiating treatment at age 40+ years (HR 1.37, 95% CI 1.29–1.45). When comparing women with a first birth at age 40+ years with or without ART treatment, the increased risk among women treated with ART persisted (HR 1.51, 95% CI 1.09–2.08). LIMITATIONS, REASONS FOR CAUTION: Although this study is based on a large, national cohort of women, more research with sufficient power and confounder adjustment is needed, particularly in cohorts with a broad age representation. WIDER IMPLICATIONS OF THE FINDINGS: An increased risk of breast cancer associated with a higher age at ART treatment initiation has been shown. Ovarian stimulation may increase the risk of breast cancer among women initiating ART treatment when aged 40+ years. Age-related vulnerability to hormone exposure or higher hormone doses during ART treatment may explain the increased risk. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by a PhD grant to D.V. from the Faculty of Health and Medical Sciences, University of Copenhagen, Denmark. Funding for establishing the DANAC II cohort was received from the Ebba Rosa Hansen Foundation. The authors report no conflict of interest. TRIAL REGISTRATION NUMBER: N/A.